Investigation of the Effect of Using Drama Techniques in Teaching English on the Attitudes of 5th-Grade Students Towards English Lessons: The Case of Elazığ Province - Akgül, Nagihan Elif; Bezgin, Merve; Kavaklı, Feyza Nur; Ayyıldız, Nilay Erdem (My University, 2025)
This research aimed to examine the effect of using role-playing and miming drama techniques in teaching English on the attitudes of 5th- grade students towards the English lessons. For this, 64 5th-grade students from two different classes at a state school in Elazığ were selected through convenience sampling. Pre-test data were obtained from the experimental group and the control group, using the reliability-tested attitude scale of Aydoğmuş (2017). Then, 10-hour lessons in which the selected drama techniques were integrated were applied to the experimental group, while the lessons continued as in the traditional way in the control group. The completion of the application was followed by the application of the same scale to obtain post-test data from both groups. The pre-test and post-test data were analyzed using the mixed-design ANOVA statistical method, and the results indicated that the drama techniques altered 5th-grade students’ attitudes towards English lessons positively.
Keywords: Role-playing; English teaching; drama techniques; miming; student attitude